A study on the localized corrosion inhibition for mild steel in saline solution - Nam, Nguyen Dang; Nguyen To Hoai,; Hien, Pham Van (Vietnam Journal of Science and Technology, 2018)
In this study, 0.45 mM yttrium 4-nitrocinnamate (Y(4NO2Cin)3) embedded in various aqueous chloride solutions, which has been studied as a possible localized corrosion inhibition system using electrochemical techniques and surface analysis. Furthermore, a wire-beam electrode (WBE) exposed to NaCl solutions containing Y(4NO2Cin)3 compound. The results indicated the possible application of a WBE in simulating and monitoring the localized corrosion inhibition. Moreover, Y(4NO2Cin)3 compound showed an excellent localized corrosion inhibition at 0.01 M due to high inhibition performance and good protective film formation. It also indicated that addition of 0.45 mM Y(4NO2Cin)3 compound increased the localized corrosion inhibition with a decrease of the Clˉ ion concentration in the investigated solutions. A new method of localized corrosion inhibition estimation has been developed using a WBE which shows a consistent result with electrochemical and surface analysis data. In addition, other electrochemical techniques and surface analysis are also used for not only ensuring but also confirming the localized corrosion inhibition.